A New User Revocable Ciphertext-Policy Attribute-Based Encryption with Ciphertext Update. (22nd December 2020) - Liu, Zhe; Wang, Fuqun; Chen, Kefei; Tang, Fei
Abstract : The revocable ciphertext-policy attribute-based encryption (R-CP-ABE) is an extension of ciphertext-policy attribute-based encryption (CP-ABE), which can realize user direct revocation and maintain a short revocation list. However, the revoked users can still decrypt the previously authorized encrypted data with their old key. The R-CP-ABE scheme should provide a mechanism to protect the encrypted data confidentiality by disqualifying the revoked users from accessing the previously encrypted data. Motivated by practical needs, we propose a new user R-CP-ABE scheme that simultaneously supports user direct revocation, short revocation list, and ciphertext update by incorporating the identity-based and time-based revocable technique. The scheme provides a strongly selective security proof under the modified decisional q -parallel bilinear Diffie–Hellman Exponent problem, where "strongly" means that the adversary can query the secret key of a user whose attribute set satisfies the challenge ciphertext access structure and whose identity is in the revocation list.